ALCOHOL AND PSYCHOACTIVE SUBSTANCE USE AMONG MEDICAL STUDENTS OF THE UNIVERSITY OF ILORIN, NIGERIA - Makanjuola, A.B.; Abiodun, O.A.; Sajo, S. (European Scientific Journal, ESJ, 2014)
The study was aimed at determining the prevalence and predictive factors associated with alcohol and other psychoactive substance use among medical students of the University of Ilorin. A self administered interview schedule consisting of WHO Students Drug Use Survey Questionnaire, and the General Health Questionnaire-12 were administered to a weighted proportionate sample of the respondents. The most currently used substances were mild stimulants (19.4%), alcohol (12.5%), hypnosedatives (3.4%), tobacco (1.7%), cannabis (1.7%), opioids (0.9%) and organic solvents (0.4%). Parents’ alcohol use, respondents perceived harm of alcohol use, level of religiosity, peers’ influence were found to have significant association with current alcohol use. There was no significant association between respondent’s perceived harm of substance use and current use of tobacco, hypnosedatives, mild stimulants and cannabis. Eighty five percent of respondents had a GHQ score of 0-2 (negative) while 14.7% had a score of 3-12 (positive). There was no significant association between psychiatric morbidity on one hand and current or lifetime substance use on the other. We concluded that while the prevalence of current use of some psychoactive substances has reduced over the past 6 years, others have increased. It was suggested that planners of medical education should continue to lay emphasis on the risks of psychoactive substance use as part of the medical school curriculum. Other governmental and non-governmental bodies should also continue to plan and implement campaigns against substance use, not only among medical students, but the society in general.